Vermögensanlage und Vermögensmanagement von Stiftungen - Lothar Hübl; Matthias Dreyer (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2005)
Investment policy is a central issue in foundations. The capital stock of a foundation and its long-term retention are prerequisites of a foundation?s perpetuity and independence. A foundation?s goals can only be reached with the funds generated by the foundation?s investment management. Ever greater demands have been placed on investment management in recent years. This paper maps out tenets of investment management that apply to all foundations, regardless of specific constraints or characteristics.
Keywords: L30; G31; L31; 330; foundation; investment management